Changes in red blood cell parameters during incremental exercise in highly trained athletes of different sport specializations - Ciekot-Sołtysiak, Monika; Kusy, Krzysztof; Podgórski, Tomasz; Pospieszna, Barbara; Zieliński, Jacek (PeerJ, 2024)
Background During physical exercise, the level of hematological parameters change depending on the intensity and duration of exercise and the individual’s physical fitness. Research results, based on samples taken before and after exercise, suggest that hematological parameters increase during incremental exercise. However, there is no data confirming this beyond any doubt. This study examined how red blood cell (RBC) parameters change during the same standard physical exertion in athletes representing different physiological training profiles determined by sport discipline. Methods The study included 39 highly trained male members of national teams: 13 futsal players, 12 sprinters, and 14 triathletes. We used multiple blood sampling to determine RBC, hemoglobin (Hb), hematocrit value (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), and red blood cell distribution width (RDW) before, during (every 3 min), and after (5, 10, 15, 20, and 30 min) an incremental treadmill exercise test until exhaustion. Results There were no significant exercise-induced differences in RBC parameters between athletic groups. No significant changes were recorded in RBC parameters during the low-intensity phase of exercise. RBC, Hb, and Hct increased significantly during incremental physical exercise, and rapidly returned to resting values upon test termination. Conclusions The general pattern of exercise-induced changes in RBC parameters is universal regardless of the athlete’s physiological profile. The changes in RBC parameters are proportional to the intensity of exercise during the progressive test. The increase in hemoglobin concentration associated with the intensity of exercise is most likely an adaptation to the greater demand of tissues, mainly skeletal muscles, for oxygen.
Keywords: Hematological parameters; Exercise test; Futsal players; Sprinters; Triathletes